J/ψ production as a function of charged particle multiplicity in pp collisions at √s =7TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad Masoodi, A.; Ahmad, N.; et al. (Elsevier, 2012)
The ALICE Collaboration reports the measurement of the relative J/𝜓 yield as a function of charged particle pseudorapidity density dNch/dη in pp collisions at √s = 7 TeV at the LHC. J/𝜓 particles are detected for pt > 0, in the rapidity interval |y| < 0.9 via decay into e⁺e⁻, and in the Interval 2.5 < y < 4.0 via decay into μ⁺μ⁻ pairs. An approximately linear increase of the J/𝜓 yields normalized to their event average (dNᴊ/ψ /dy)/⟨dNᴊ/ψ/dy⟩ with (dNch/dη)/⟨dNch/dη⟩ is observed in both rapidity ranges, where dNch/dη is measured within |η| < 1 and pt > 0. In the highest multiplicity Interval with ⟨dNch/dη(bin) ⟩ = 24.1, corresponding to four times the minimum bias multiplicity density, an enhancement relative to the minimum bias J/𝜓 yield by a factor of about 5 at 2.5 < y < 4 (8 at |y| < 0.9) is observed.
Keywords: Quarkonium production; pp collisions; https://purl.org/pe-repo/ocde/ford#1.03.03